U.S. State and Local Government Finances Over the Current Cycle - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 1992)
The recent slowdown in the U.S. economy has led to state and local government tax increases and expenditure cuts that have lowered aggregate demand, in contrast to earlier downturns when the sector provided significant automatic stabilizers. Several explanations for this change are examined, including the role of federal grants, mandates, tax revolts, and compensation. The first three factors are found to be relatively unimportant. There does, however, appear to have been a large change in relative compensation over the 1980s, which can account for much of the deterioration in finances.